Les dossiers d’action publique, des registres criminels de 1791 à la dématérialisation - Manuel Toulajian (In Situ)
The Ministry of Justice’s collections of public prosecution, from the first criminal registers established as early as the creation of the ministry in 1791 until the virtual disappearance of paper documents in 2016 under the influence of digitisation, are of a major heritage interest for the history of crime and more broadly for the political, economic and social history of contemporary France. For more than two centuries, the files composing the collections have reported the public prosecution for the enforcement of sentences, this judicial process which leads, throughout the national territory, to sanction criminally an offender. This process produces documents (mainly notes and reports), submitted by the Prosecutor’s Offices to Chief public Prosecutors, before they are centralised by the “direction des Affaires criminelles et des Grâces”, the Directorate for Criminal Affairs and Pardons (DACG).The departmental (an II-1816), chronological (1814-1955), methodical (1890-1955) and current series (1956-1994), all kept in the National Archives (AN), constitute, with the associated registers of the subseries BB/29, a source of over 10,000 articles and of nearly two linear kilometres. To these largely unexplored sources of a nation under construction, that then underwent two world wars and their consequences, were added dozens of thousands records of public prosecution for the period 1995-2014 (1,2 kml) managed by the department of archives, documentation and heritage (DADP) of the Ministry of Justice. These records are evidence of a strong growth of financial crime, while in the paper and digital sets which are still kept place Vendôme (2015-2021), cases linked to offences of a terrorist nature are beginning to emerge.At both ends of these archival fonds, two media linked by the same object, public prosecution, look at each other, fragile: the just born old criminal register of the ministry and the digital native document whose sustainability challenge is becoming an essential issue for the operation of justice and the build-up of its archival heritage.